Rates of invasive disease and outcomes in NSCLC patients with biopsy suggestive of carcinoma in situ. (July 2021) - Talcott, Wesley J.; Miccio, Joseph A.; Park, Henry S.; White, Abby A.; Kozono, David E.; Singer, Lisa; Sands, Jacob M.; Sholl, Lynette M.; Detterbeck, Frank C.; Mak, Raymond H.; Decker, Roy H.; Kann, Benjamin H.
Highlights: For NSCLC with biopsy suggestive of in situ disease, 49.3 % had invasion at resection. Size and squamous histology were significantly associated with risk of invasion. Even lesions with the most favorable characteristics, invasion was present in 38.2 %. Nearly 30 % of biopsied lesions were observed, with 3 year OS in this cohort 51.5 %. This supports definitive therapy for NSCLC with biopsy suggestive of in situ disease. Abstract: Introduction: Carcinoma in situ is a rare non-invasive histology of non-small cell lung cancer (NSCLC) with excellent survival outcomes with resection. However, management of lung biopsy suggestive of in situ disease remains unclear. To inform decision-making in this scenario, we determined the rate of invasive disease presence upon resection of lesions with an initial biopsy suggestive of purely in situ disease. Methods: The study included 960 patients diagnosed with NSCLC from 2003 to 2017 in the National Cancer Database whose workup included a lung biopsy suggestive of in situ disease. Among the cohort who proceeded to resection, we identified the rate of invasive disease discovered on surgical pathology along with significant demographic and clinical contributors to invasion risk. Survival outcomes were measured for the observed cohort that did not receive local therapy after biopsy. Results: Invasive disease was identified at resection in 49.3 % of patients. Lesion size was associated with risk of invasive disease: 35.7 % for ≤1 cm, 45.2 % for 1−2 cm, 55.7 % for 2−3 cm, and 87.5 % for 3−5 cm (p < 0.001). Of patients with squamous histology, 61.5 % had invasive disease versus 46.5 % with adenocarcinoma histology (p = 0.026). On multivariable logistic regression, invasive disease remained associated with tumor size (OR 1.9 per cm, 95 % CI 1.5–2.4, p < 0.001), and squamous histology (OR 1.8, 95 % CI 1.1–3.2, p = 0.028). Overall survival at 3 years was 51.5 % in the observed cohort. Conclusion: Nearly half of patients with biopsy suggestive of in situ disease had invasive disease at resection. Tumor size and histology are strong predictors of invasive disease and may be used for risk stratification. However, the findings support the practice of definitive therapy whenever feasible.